Gender Diversification in The Perspective of Accounting Fraud: A Literature Review Study - Susmita Dian Indiraswari; Lilik Purwanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Gender diversification or gender diversity refers to efforts to increase the representation and participation of individuals from diverse gender backgrounds in the workplace. Accounting fraud, on the other hand, refers to practices carried out by individuals or organizations to manipulate financial information for personal or organizational gain. This article provides an overview of gender diversification in the perspective of accounting fraud using a qualitative approach and literature review method. Content analysis is the analysis technique used in this literature review research to prevent possible misinterpretation due to the researcher's lack of knowledge or insufficient information in the literature. The research report is written in a simple and easy-to-understand language, considering the researcher's limitations in conducting an in-depth and detailed study. The principle of simplicity and ease is applied to ensure that the content of the counseling and guidance program evaluation report can be easily understood by readers